EDUKASI TINGKAT PERJENJANGAN BUKU UNTUK PENINGKATAN MUTU PENDIDIKAN DAN PEMBELAJARAN - I Gede Bayu Kusuma; Made Ngurah Suragangga (UHN IGB Sugriwa Denpasar, 2025)
Books play a significant role in improving the quality of education in Indonesia, and even globally. Books are now starting to adapt to more contextual changes. In today's era, many readers, including parents and communities, have expressed concerns about the mismatch between language use and the age context or students' comprehension of the provided materials. It is crucial for educational organizers, publishers, authors, and the broader community to understand the context of book leveling for both textbooks and non-textbooks used in schools and education in Indonesia. Education and awareness regarding book leveling can help prevent students or learners from accessing unsuitable reading materials and prevent the circulation of books that violate educational provisions, thus ensuring optimal literacy quality. Book leveling is regulated under Regulation No. 30 of 2022 issued by the Head of the Agency for Education Standards, Curriculum, and Assessment (BSKAP). This regulation is also part of the implementation of Law No. 3 of 2017 on the National Book System. This regulation defines Leveled Books as books containing text/images and language that gradually increase in complexity from simple to more challenging as a reading challenge. The levels are as follows: Level A or Beginner Reader Level: Readers at this level are introduced to books for the first time and require scaffolding to assist them in reading. Level B or Early Reader Level: Readers require scaffolding and can read text in the form of words/phrases with a combination of letter sounds, clauses, and simple sentences. Level C or Intermediate Reader Level: Readers can fluently read texts in paragraph form within a discourse. Level D or Advanced Reader Level: Readers can comprehend various texts of moderate difficulty. Level E or Proficient Reader Level: Readers can critically and analytically read various reading sources to synthesize thoughts more effectively. Keywords: Book Leveling, Literacy, Reading Skills